Δ-Tocopherol prevents methylglyoxal-induced apoptosis by reducing ROS generation and inhibiting apoptotic signaling cascades in human umbilical vein endothelial cells1. Issue 5 (13th May 2015) - Do, Moon ho; Kim, Su nam; Seo, Seung-Yong; Yeo, Eui-Ju; Kim, Sun Yeou
<x xml:space="preserve">Abstract</x> δ-Tocopherol protects HUVECs against apoptotic activity induced by methylglyoxal.